The Strategic Role of School Administration in Achieving Stakeholder Satisfaction: A Case Study in Indonesian Schools in Riyadh - Sakinah; Kaniati Amalia; Ainur Rifqi; Amrozi Khamidi; Mochamad Nursalim; Erny Roesminingsi (Papanda Publisher, 2026)
This study examines the strategic role of school administration in achieving stakeholder satisfaction at the Indonesian School of Riyadh, an international institution serving the Indonesian diaspora in Saudi Arabia. Given the multicultural student population and the demands of maintaining Indonesian cultural identity while adhering to international educational standards, effective school administration plays a pivotal role in creating a conducive learning environment that supports holistic student development. This research employed a qualitative case study approach, utilizing semi-structured interviews with 55 participants (10 administrators, 15 teachers, 20 parents, and 10 students), focus group discussions, and comprehensive document analysis. The study found that 87% of teachers and 85% of parents reported high satisfaction with administrative communication and transparency, while 80% of students expressed positive perceptions regarding fairness in administrative policies. The findings reveal that effective administrative practices, characterized by transparent communication, equitable policy implementation, and proactive problem-solving approaches, significantly contribute to enhanced satisfaction levels among students, parents, and teachers. The study demonstrates that inclusive and collaborative leadership by the principal strengthens positive school climate, increases stakeholder engagement, and builds sustainable trust within the educational community. Furthermore, the research highlights the critical importance of implementing multicultural approaches in administrative practices to ensure cultural diversity is valued and embraced, thereby creating an inclusive educational environment. However, the study identified specific areas requiring improvement, including expanding opportunities for teacher participation in collaborative planning processes and providing more frequent and detailed updates on student academic progress to parents. These findings provide valuable insights for international schools seeking to optimize administrative practices to enhance educational quality and achieve comprehensive stakeholder satisfaction in multicultural educational contexts.